Analysis of Consumer Satisfaction with the Reward Zone Feature for Traveloka Application Users - Mita Agustia; Muhammad Riyan Pradana; Muhammad Zacky; Khairani Zikrina; Zulfa Fahmy (LPPM Institut Studi Islam Sunan Doe, 2024)
Consumer satisfaction is a feeling that is owned by someone either happy or disappointed. This study aims to determine customer satisfaction with Traveloka services contained in the reward zone feature. This research uses a qualitative approach with the focus group discussion method which takes place on Google Meet. The subjects of this study were 11 students of UIN Walisongo Semarang. This research was conducted for 1 month. The results of the study show that consumer satisfaction with the reward zone feature is quite significant. The results of consumer satisfaction research on the reward zone feature are determined by consumers, consumers also give an average rating of 6.7/10 from several consumers and give reasons.